Psychiatry Engagement in The Management of Delirium in General Hospital Patients - Wan-Lin Cheng; Szu-Hsien Chiang; Pei-Chi Liu; Lin, Chien-ho (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Delirium is a common and serious problem in patients with medical illness. The overall prevalence rate of delirium was 10 31% in hospital general medical in-patient settings. The purpose of this study is to examine the characteristics of patients with delirium encountered during the consultation of psychiatric departments in other departments of general hospitals, the benefit of consultation. Methods: We reviewed the medical records to collect relevant information. The Confusion Assessment Method-Short (CAM-Short) scale was used to evaluate the severities. Results: Twenty patients were recruited. The average age was 73.9-year-old. All the participants presented with hyperactive delirium. The average initial CAM score was 4.5 and then decreased to 2 after the follow-up. Almost all teams applying for consultation arranged treatment (19 in 20) or examinations (18 in 20) as the suggestion.. Conclusion: In our study, the psychiatric department's consultation services have specific assistance to patients with delirium. The consulting physician should still track the follow-up status of the case and discuss the treatment of delirium with other physicians at an appropriate time. Keywords: Delirium, psychiatric consultation, CAM-S